Hormone Replacement Therapy Reverses Gut Microbiome and Serum Metabolome Alterations in Premature Ovarian Insufficiency - Jiang, Lingling; Fei, Haiyi; Tong, Jinfei; Zhou, Jiena; Zhu, Jiajuan; Jin, Xiaoying; Shi, Zhan; Zhou, Yan; Ma, Xudong; Yu, Hailan; Yang, Jianhua; Zhang, Songying (Frontiers in Endocrinology, 2021)
Objective: We explored the gut microbiome and serum metabolome alterations in patients with premature ovarian insufficiency (POI) and the effects of hormone replacement therapy (HRT) with the aim to unravel the pathological mechanism underlying POI. Methods: Fecal and serum samples obtained from healthy females (HC, n = 10) and patients with POI treated with (n = 10) or without (n = 10) HRT were analyzed using 16S rRNA gene sequencing and untargeted metabolomics analysis, respectively. Peripheral blood samples were collected to detect serum hormone and cytokine levels. Spearman’s rank correlation was used to evaluate correlations between sex hormones and cytokines and between the gut microbiota and serum metabolites. To further confirm the correlation between Eggerthella and ovarian fibrosis, the mice were inoculated with Eggerthella lenta (E. lenta) through oral gavage. Results: The abundance of genus Eggerthella significantly increased in the fecal samples of patients with POI compared to that observed in the samples of HCs. This increase was reversed in patients with POI treated with HRT. Patients with POI showed significantly altered serum metabolic signatures and increased serum TGF-β1 levels; this increase was reversed by HRT. The abundance of Eggerthella was positively correlated with altered metabolic signatures, which were, in turn, positively correlated with serum TGF-β1 levels in all subjects. Estrogen ameliorated ovarian fibrosis induced by E. lenta in mice. Conclusions: The interactions between the gut microbiota, serum metabolites, and serum TGF-β1 in patients with POI may play a critical role in the development of POI. HRT not only closely mimicked normal ovarian hormone production in patients with POI but also attenuated gut microbiota dysbiosis and imbalance in the levels of serum metabolites and TGF-β1, which are reportedly associated with fibrosis. The findings of this study may pave the way for the development of preventive and curative therapies for patients with POI.